Photoinduced Proton‐Transfer Reactions for Mild O‐H Functionalization of Unreactive Alcohols. Issue 14 (25th February 2020) - Jana, Sripati; Yang, Zhen; Li, Fang; Empel, Claire; Ho, Junming; Koenigs, Rene M.
Abstract: Hexafluoroisopropanol is typically considered as an unreactive solvent and not as a reagent in organic synthesis. Herein, we report on a mild and efficient photochemical reaction of aryl diazoacetates with hexafluoroisopropanol that enables, under stoichiometric reaction conditions, the synthesis of fluorinated ethers in excellent yield. Mechanistic studies indicate there is a preorganization of hexafluoroisopropanol and the diazoalkane acts as an unreactive hydrogen‐bonding complex. Only after photoexcitation does this complex undergo a protonation‐substitution reaction to the reaction product. Investigations on the applicability of this photochemical transformation show that a broad variety of acidic alcohols can be subjected to this transformation and thus demonstrate the feasibility of this concept for O‐H functionalization reactions (54 examples, up to 98 % yield). Abstract : A light‐bulb moment : Photoinduced proton‐transfer reactions of diazoacetates enable the highly efficient O‐H functionalization of halogenated, unreactive alcohols under stoichiometric reaction conditions. This approach offers a new reactivity pattern of diazoacetates.